Analysis of human peripheral blood T cells and single-cell-derived T cell clones uncovers extensive clonal CpG island methylation heterogeneity throughout the genome - Zhu, Xiaoxiang (The National Academy of Sciences, 1999)
Methylation of cytosine residues in CpG dinucleotides is generally associated with silencing of gene expression. DNA methylation, as a somatic event, has the potential of diversifying gene expression in individual cells of the same lineage. There is little quantitative data available concerning the extent of methylation heterogeneity in individual cells across the genome. T cells from the peripheral blood can be grown as single-cell-derived clones and can be analyzed with respect to their DNA methylation patterns by restriction landmark genomic scanning. The use of the methylation-sensitive enzyme NotI to cut and end-label DNA fragments before their separation in two dimensions provides a quantitative assessment of methylation at NotI sites that characteristically occur in CpG islands. We have undertaken quantitative analysis of two-dimensional DNA patterns to determine the extent of methylation heterogeneity at NotI sites between peripheral blood single-cell-derived T cell clones from the same individual. A total of 1,068 NotI-tagged fragments were analyzed. A subset of 156 fragments exhibited marked methylation heterogeneity at NotI sites between clones. Their average intensity among clones correlated with their intensity in uncultured, whole-blood-derived T cells, indicating that the methylation heterogeneity observed in clones was largely attributable to methylation heterogeneity between the individual cells from which the clones were derived. We have cloned one fragment that exhibited variable NotI-site methylation between clones. This fragment contained a novel CpG island for a gene that we mapped to chromosome 4. The methylation status of the NotI site of this fragment correlated with expression of the corresponding gene. Our data suggest extensive diversity in vivo in the methylation and expression profiles of individual T cells at multiple unrelated loci across the genome.